Influence of organic aerosol molecular composition on particle absorptive properties in autumn Beijing - J. Cai; J. Cai; C. Wu; J. Wang; W. Du; W. Du; F. Zheng; S. Hakala; S. Hakala; X. Fan; B. Chu; B. Chu; et al. (Atmospheric Chemistry and Physics, 2022)
Organic aerosol (OA) is a major component of fine particulate matter (PM), affecting air quality, human health, and the climate. The absorptive and reflective behavior of OA components contributes to determining particle optical properties and thus their effects on the radiative budget of the troposphere. There is limited knowledge on the influence of the molecular composition of OA on particle optical properties in the polluted urban environment. In this study, we characterized the molecular composition of oxygenated OA collected on filter samples in the autumn of 2018 in Beijing, China, with a filter inlet for gases and aerosols coupled to a high-resolution time-of-flight chemical ionization mass spectrometer (FIGAERO–CIMS). Three haze episodes occurred during our sampling period with daily maximum concentrations of OA of 50, 30, and 55 µg m−3. We found that the signal intensities of dicarboxylic acids and sulfur-containing compounds increased during the two more intense haze episodes, while the relative contributions of wood-burning markers and other aromatic compounds were enhanced during the cleaner periods. We further assessed the optical properties of oxygenated OA components by combining detailed chemical composition measurements with collocated particle light absorption measurements. We show that light absorption enhancement (Eabs) of black carbon (BC) was mostly related to more oxygenated OA (e.g., dicarboxylic acids), likely formed in aqueous-phase reactions during the intense haze periods with higher relative humidity, and speculate that they might contribute to lensing effects. Aromatics and nitro-aromatics (e.g., nitrocatechol and its derivatives) were mostly related to a high light absorption coefficient (babs) consistent with light-absorbing (brown) carbon (BrC). Our results provide information on oxygenated OA components at the molecular level associated with BrC and BC particle light absorption and can serve as a basis for further studies on the effects of anthropogenic OA on radiative forcing in the urban environment.